Resultados de la interacción con la comunidad en la formación universitaria desde el enfoque de las capacidades. Un estudio de caso en la Universidad Nacional de Costa Rica - Monge Hernández, Carmen (Universidad Nacional del Litoral, 2018)
This work aimed analyze an experience of how scholar actions work in an integral manner and based on the university extension done by the Escuela de Planificación y Promoción Social (EPPS) of National University, Costa Rica (UNA). Our purpose is to contribute on the understanding of some of the formation benefits derived from the university and community work done by economic and social planning students, using the capability approach for human development promoted by Sen and Nussbaum. The results highlight a great richness regarding to the formation processes based on a dialogical and participatory relation, as well as interaction and building up knowledge, all of which is important in human development. Students interact with the most vulnerable groups that are far from the State policy benefits through the methodologic and theoretical knowledge acquired on their formation and complemented with other knowledge. This promotes meaningful learning that increases sensibility, strengthens social values and improves analysis and critical comprehension of social needs. As a result, students have the opportunity of a scholar formation that is integral and humanistic.